Isolation and evaluation of antiglycation potential of polyalthic acid (furano-terpene) from Daniella oliveri - Olubunmi Atolani; Gabriel A. Olatunji (Elsevier, 2014)
A furano-diterpene (polyalthic acid) was isolated as a major stable compound for the first time from the oleoresin of the Daniella oliveri of the family Caesalpiniacea through column chromatography fractionation. Polyalthic acid was characterized using data obtained from EIMS, HREIMS, ESI-MS, MALDI-MS as well as 1D and 2D NMR and it was evaluated for its potential to inhibit the formation of advanced glycation end-products (AGEs) using a standard in vitro antiglycation procedure. Polyalthic acid indicated a negative antiglycation potential compared to standard inhibitor that has 85% inhibition, which is an indication that polyalthic acid may not contribute to the antiglycation activity of the plant as acclaimed in folkloric medicine. The negative antiglycation observed could indicate that the polyalthic acid could trigger glycation, thereby subjecting users to various degrees of complications. The bioactivity evaluation on molinspiration evaluator indicated that polyalthic acid could be a potential drug candidate. The biological and chemical insights gained on polyalthic acid provide a good basis for future research. Keywords: Daniella oliveria, Polyalthic acid, Furano-diterpene, Antiglycation, Matrix assisted laser desorption/ionization (MALDI)